Comparative study of soil amendment and organic fertilizer use to optimize agricultural dryland - Suherman, Suherman; Kurniawan, Edi; Asysyuura, Asysyuura; Asmi, Husni; Fitriani, Indah; Zulkifli, Zulkifli; Fatwa, Abdul Halil (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2025)
This study investigates the effects of different organic soil amendments on the chemical characteristics of dryland soils to enhance agricultural practices in arid areas. Employing a randomized complete block design, six treatments were administered oversix-months on acidic soils with low organic matter concentration, exemplifying typical dryland conditions in tropical areas. The treatments comprised high and moderate doses of mixed organic compounds, alongside control groups without amendments. Soil samples were analyzed pre- and post-treatment for pH, carbon, nitrogen, phosphorus, and potassium concentrations. Results demonstrate that high-dose organic mixtures markedly enhanced soil pH, carbon content, and nutrient availability, particularly phosphorus and potassium, in comparison to control and lower-dose treatments. The research underscores the essential importance of suitable amendment kinds and quantities in improving soil quality and sustainability. The findings indicate that the strategic application of organic amendments can markedly enhance the chemical properties of dryland soils, hence promoting more sustainable farming operations.